Improving Civics Learning Outcomes through Discussion Method for Fifth Grade Students at SDN Kesek 1 - Lia Hadini; Ziyanatul Fitriyah; Novianti Romadani; Agung Setyawan; Usani Joseph Ofem (Sekolah Tinggi Agama Islam Nurul Islam Mojokerto, 2025)
This research aims to improve civics learning outcomes of fifth grade students at SDN Kesek 1 through the application of the discussion method. This research is classroom action research with the research subjects being fifth grade students at SDN Kesek 1 for the 2023/2024 academic year, totaling 32 students with minimum completion criteria of 75% individual and 80% classical. Data collection techniques using interview, observastion, tests and documentation with data collection instruments using interview sheets, teacher and student activity observation sheets, teaching modules and question sheets. The data analysis technique used is quantitative descriptive. The research results showed that teacher activities in cycle I, namely 68,75% and increased in cycle II, namely 81,25%. Student activities in cycle I, namely 64,06% and increased in cycle II, namely 82,81%. Student learning outcomes in cycle I, namely 71,87% and increased in cycle II, namely 87,5%. Based on from the research data, it can be concluded that through the application of the discussion method, student learning outcomes in civics learning can be improved fifth grade students of SDN Kesek 1.